Measuring 21st-century science laboratory competence: development and validation of a contextual assessment tool - Andina Nurul Wahidah; Inayah Dzil Izzati Hartono (Yayasan Insan Mulia Bima, 2026)
Mastery of contextual experiment-based science laboratory competencies is essential for strengthening scientific literacy, critical thinking, and data interpretation skills in the 21st century. However, there is a lack of standardized instruments that holistically measure conceptual, procedural, and interpretative dimensions, particularly at the secondary education level. This study aimed to develop and validate an assessment instrument for Contextual Experiment-Based Biology Laboratory Competency using a limited research and development (R&D) design. Instrument development involved theoretical analysis, blueprint construction, expert validation, pilot testing, Exploratory Factor Analysis (EFA), and Rasch model analysis. Item development was grounded in literature review, national curriculum guidelines, and locally relevant experimental contexts integrated into students’ learning experiences. Content validation by eight experts using I-CVI and S-CVI yielded high agreement (I-CVI ≥ 0.87; S-CVI = 0.95). Construct validity was examined using Exploratory Factor Analysis (EFA) with Maximum Likelihood extraction and Promax rotation on trial data from 135 Madrasah Aliyah students. The results showed a KMO value of 0.75 and a significant Bartlett’s Test (p < 0.001). Three major factors emerged, explaining 43.0% of the total variance and aligning with the initial construct framework. Further calibration using the Rasch Model demonstrated good item fit, high reliability (0.86), and well-distributed item logits. The instrument proved valid and reliable as a diagnostic assessment tool based on contextual experimentation. The findings support the implementation of authentic, context-based assessment and recommend follow-up CFA analysis and practical application in biology laboratory instruction.